2010
DOI: 10.5194/nhess-10-1751-2010
|View full text |Cite
|
Sign up to set email alerts
|

Ionospheric anomaly due to seismic activities – Part 2: Evidence from D-layer preparation and disappearance times

Abstract: Abstract. We show evidences for anomalous ionospheric behaviour in the signal of Indian navy VLF transmitting station named VTX due to earthquakes in the South Asian region. We concentrate on the variation of the D-layer preparation time (DLPT) and D-layer disappearance time (DLDT) in a period of sixteen months and study their average behaviors. We identify those days in which DLPT and DLDT exhibit significant deviations. Separately, we compute the energy release by earthquakes during this period and show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(34 citation statements)
references
References 11 publications
0
34
0
Order By: Relevance
“…The conclusion claimed by these authors is that ionospheric perturbations by means of the subionospheric VLF/LF data tend to definitely take place before an EQ when the EQ magnitude is greater than 5.5 and when the depth is shallow (d < 40 km). Also, a statistical study using an Indian transmitter has been done by Chakrabarti et al (2010), who have shown a possible correlation with EQs. Recently, two papers have been published about the rather complete statistical correlation between the ionospheric perturbation and EQs over nine years by using different VLF/LF propagation paths (Hayakawa et al, 2010a, b).…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion claimed by these authors is that ionospheric perturbations by means of the subionospheric VLF/LF data tend to definitely take place before an EQ when the EQ magnitude is greater than 5.5 and when the depth is shallow (d < 40 km). Also, a statistical study using an Indian transmitter has been done by Chakrabarti et al (2010), who have shown a possible correlation with EQs. Recently, two papers have been published about the rather complete statistical correlation between the ionospheric perturbation and EQs over nine years by using different VLF/LF propagation paths (Hayakawa et al, 2010a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Various causes of disturbances have been identified mainly from space and tropospheric phenomena. Therefore VLF signals contain information about an evolution of the lower ionosphere (e.g., D-layer formation and disappearance time) (Chakrabarti et al, 2010), space weather effects such as geomagnetic storms (Kikuchi and Evans, 1983), effects of solar flares and solar energetic particles events (Mitra, 1974;Thomson and Clilverd, 2001;Todoroki et al, 2007), lightning-induced energetic particle precipitations and direct heating due to intensive lightning discharges and Transient Luminous Events (TLEs) (Inan et al, 1985(Inan et al, , 1988Hobara et al, 2001) and even effects of strong gamma ray bursts far away beyond the solar system (Tanaka et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In Chakrabarti et al (2007) a preliminary discussion was made to show that these quantities may also be used to study ionospheric anomalies. In our next paper, (Chakrabarti, Sasmal and Chakrabarti, 2009) we will show the correlations of DLPT and DLDT with the seismic activities.…”
Section: Discussionmentioning
confidence: 97%